Embracing Innovative Approaches in Data Science: Investigating Contemporary Trends in Data Collection, Analysis, and Visualization Methods - Ramalakshmi, S.; Asha, G. (Journal of Trends in Computer Science and Smart Technology, 2023)
Today businesses are becoming more productive and their return on investment (ROI) is increasing with the development of new technologies like data science, artificial intelligence and data analytics. In today’s trend organizations are dealing with big data and these data can drive the whole organization in many ways. The process of doing data analysis and extracting meaningful insight is known as data science. Most business organizations are taking data driven models to ease their work and for making intelligent business decisions. The life cycle of a data science involves so many steps like understanding the business, data collection, analysis and data modelling etc., and to achieve these steps various new technologies and methods are available. Firstly, the process of data collection has been significantly augmented by artificial intelligence, allowing businesses to gather vast amounts of structured and unstructured data efficiently. This rich pool of data serves as the foundation upon which strategic decisions are made. By leveraging advanced data collection methods, organizations gain invaluable insights into market trends, customer behaviour, and operational patterns, empowering them to make informed, data-driven decisions. Secondly, data analysis, a core element of data science, plays a pivotal role in extracting meaningful insights from the collected data. Through sophisticated analytical techniques, businesses can uncover hidden patterns, correlations, and trends within the data. This deep understanding of the data not only facilitates efficient problem-solving but also enables the identification of opportunities for innovation and growth. Informed by data analysis, businesses can optimize processes, identify cost-saving measures, and enhance overall operational efficiency. Lastly, data visualization techniques such as real-time visualization and augmented analytics empower organizations to transform complex data sets into easily understandable visual representations. Real-time visualization provides businesses with up-to-the-minute insights, enabling them to respond promptly to market changes and emerging trends. Augmented analytics, on the other hand, leverages machine learning algorithms to automate data analysis and present actionable insights in an intuitive manner, further accelerating the decision-making process. In this study the recent trends in data science like artificial intelligence for data collection, augmented analytics and predictive analysis for data analysis and data democratization & real time visualization techniques for data visualization are discussed in detail. This study also presents the tools, key challenges and applications of these recent methods in brief.